The Common Agricultural Policy as Driver of the Circular Economy in the European Union: The Case of Romania - Andreea - Emanuela DRĂGOI; Cornelia NEAGU; Anca - Cătălina DRAGOMIR (Communications of International Proceedings, 2023)
The circular economy remains a central theme for the European Union’ (EU) future development all the more now during the current energy crisis generated and exacerbated by the war in Ukraine. The energy crisis has unravelled the need to cut loose the fossil fuel dependency as the main engine for the European economy, while highlighting the pressing need for encouraging the green economic development. Under the Green Deal agenda many progresses have been achieved in the Member States, but the current paper aims to underline how those progresses have been accomplished in the field of the rural development. It is currently well agreed that the Common Agricultural Policy (CAP) has shifted its core interest through greening process especial in the rural development field. Under the new Green Agenda the Member States have been encouraged to pursue the sustainable rural development goals especially through specific actions and measures under CAP Second Pillar. Our main research objective is to highlight the progresses and shortcomings of CAP Green Agenda, using a comparative analysis based on selected indicators, but also a case study about Romania. Our main conclusion points out that while CAP Strategic Plan may be a useful tool for achieving sustainable rural development, many progresses are still needed to achieve several of the circular economy goals, especially those related to the green energy development. CAP has two pillars: First Pillar dedicated to agriculture and markets and the Second Pillar that aims specifically for the financing of the rural development in all the Member States. The two pillars have different financing funds, but they are mandatory for any CAP Strategic Plan from a Member States.
Keywords: circular economy; green energies; Common Agricultural Policy (CAP); Romania’s CAP Strategic Plan; climate and action measures; rural development